Best Practices on Financial Management: A Collaborative Academic Interventions in Cotabato City, Southern Philippines - Salam, Norodin; Sedik-Salam, Marwisa (JPAIR Multidisciplinary Research, 2018)
Finance has been described as a great challenge for every organization and considered   the lifeblood of every institution which is used to finance its programs and services.  The study determined the best financial management practices and the implementation in the local government unit of Cotabato City, Mindanao, Southern Philippines.  It also identified the gaps in financial management in its covered local community.  Interview guides and document analysis were used in the study. Using descriptive method, it was found out that the financial management of the local community was properly managed. Hence, there was a good financial management in terms of finances of the communities in Cotabato City as a basis of receiving the award of the seal of good housekeeping.  It has been highly recommended to engage more trainings on the same field with the involvement of the second liner young officials.  This study provides empirical data to the agency administrators managing the community.  There will also be an identification of strategies to be adapted in the programs for implementation.
Keywords: Financial management; strategies; descriptive design; interventions; Philippines